Penggunaan Media Video Pembelajaran Berbasis Kontekstual Pada Materi Fungi Untuk Meningkatkan Hasil Belajar Kelas X Di SMA NU Juntinyuat - Reiza Fitri Yulia; Anda Juanda; Asep Mulyani (Pendidikan Fisika, FKIP, Universitas Nahdlatul Ulama Cirebon, 2021)
The Contextual-based videos link material with concepts contained in real life. So, it produces learning that is appropriate to student context. Contextual learning emphasizes the process of full student involvement to be able to understand the material being studied and relate it to life situations. This study aims to determine the differences in the improvement of learning outcomes, learning activities, and student learning responses to the use of contextual-based instructional video media. Data collection techniques used were observation, tests, and a survey to respondents in the form of questionnaire questions on contextual-based learning video assessments. The research was conducted at SMA NU Juntinyuat. The design of this study was the Control Group Pretest-Posttest design. One group was given a treatment (experimental group) and the other was not treated (control group). The results showed that: (1) there was a significant difference in student learning outcomes between the experimental class and the control class, (2) the average percentage of student learning activities increased to 92%. (3) The percentage of the average student response questionnaire as a whole is 83% with very strong criteria.